الإعلام الجديد: قراءة في تطور المفهوم والوظيفة - ضيات خـلفـلاوي, الدكتورة: شمـس (Sciences de l'Homme et de la Société, 2015)
يعيش المجتمع المعاصر تحولات هائلة في مجال الاتصال والإعلام أدت في السنوات الأخيرة إلى تغيرات كبيرة في أساليب إنتاج وتوزيع وتلقي المعلومات. فقد ظهرت تقنيات وأساليب اتصالية حديثة، وانتشرت عن طريقها خصائص ووظائف اتصالية جديدة، من أهمها التحول من وسائل الاتصال الجماهيري ذات الاتجاه الواحد، والمحتوى المتجانس، إلى تقنيات الاتصال التفاعلية ذات الاتجاهين، والمضامين المتعددة، وظهر مصطلح (الإعلام الجديد) للتعبير عن هذه الظواهر الجديدة. ويسعى هذا البحث إلى الكشف عن سمات الإعلام الجديد من حيث تطور المفهوم والوظائف في ظل هذه التطورات السريعة.   Abstract : The contemporary society is living massive shifts in the field of Media and Communication which led to significant changes in the methods of producing, distributing and receiving information in recent years. As a modern communication techniques and methods has appeared, and through them a new communication characteristics and tasks have spread, the most important of them are the transformation from the mass communications with one – way, and homogenized content to the interactive communication techniques with two – ways, and the multiple implications and then the term of the new media or the digital media has appeared for expressing these new phenomenon. This research seeks to detect new media attributes in terms of the evolution of the concept and functions under these rapid developments.